Individual and community-level factors associated with khat (Catha edulis) use among women of reproductive age in Halaba zone, South Ethiopia: a multilevel mixed effect analysis - Wogayehu, Biruk; Demissie, Tsegaye; Wolka, Eskinder; Alemayehu, Mekuriaw; Daka, Kassa (Frontiers in Psychiatry, 2024)
There is a paucity of data on factors associated with khat chewing among women of reproductive age using multilevel analysis. Therefore, this study aimed to examine the prevalence and multilevel factors associated with khat use among women of reproductive age in Halaba zone, South Ethiopia.Methods: A community-based cross sectional study was conducted in Halaba zone from February to July, 2023. Systematic random sampling technique was used to include 1573 study participants. The dependent variable was current khat use, which is operationalized as using khat within 30 days preceding the study. An interviewer administered questionnaire was used for the data collection.: The prevalence of current khat use among women of reproductive age was 65.9% [95%CI (63.5-68.2%)]. Factors significantly associated with khat use were; ages of women 35 and above years [Adjusted Odds Ratio (AOR) = 6.35, 95% CI: (3.62, 11.13)], ever married [AOR = 2.41, 95% CI: (1.10, 5.31)], secondary and above education [AOR = 0.28, 95% CI: (0.15, 0.49)], belong to richer household [AOR = 1.75, 95% CI: (1.12, 2.75)], mass media use [AOR = 3.12, 95% CI: (1.85, 4.81)], low knowledge about khat effects [AOR = 3.12, 95% CI: (1.85, 5.24)], positive attitude towards khat use [AOR = 11.55, 95% CI: (6.76, 19.71)], and strong social support [AOR = 0.43, 95% CI: (0.28, 0.64)] and non-user friend [AOR = 0.31, 95% CI: (0.20, 0.48)]. From the community level variables: rural residence [AOR = 5.06, 95% CI: (1.82, 14.09)] was significantly associated with khat use. Conclusions: Khat use among women of reproductive age was found to be very high. From individual-level factors: advanced ages of women, secondary and above education, live in the richer wealth quintile, mass media exposure, low knowledge on khat effects, positive attitude towards khat use, strong social support, and from community-level variables: residing in rural area were significantly associated with khat use. Khat use screening for all women of childbearing age, as well as referral to substance use disorder centers for those women identified as having khat use disorder, should become a standard of care in all health facilities.